How Informed are They? Coverage of Prostate Cancer Issues by Select Mainstream Newspapers in Nigeria - Ezegwu Daniel; Obichili Mercy Ifeyinwa; Nwokeocha Ifeanyi Martins; Esther George Ntegwung (QISTINA: Jurnal Multidisiplin Indonesia, 2022)
This paper focused on coverage of prostate cancer issues by select mainstream newspapers in Nigeria. The aims were to: Find out the frequency of coverage given to prostate cancer issues in Nigerian newspapers, determine the level of prominence given to prostate cancer issues in Nigerian newspapers and ascertain the story formats that are predominant in the coverage of prostate cancer issues in Nigerian newspapers. This study adopted content analysis method and two mainstream newspapers were selected in Nigeria; The Guardian and Vanguard newspapers. The period of study was six months (March 1st to August 31st, 2022). The findings revealed that the select newspapers did not report prostate cancer issues adequately and frequently in Nigerian newspapers. Further findings showed that 88% of the stories on prostate cancer were placed on the inside pages of the newspapers. Thus, the issue was not given prominence. Also, straight news format was predominantly used by the two newspapers in reporting prostate cancer in Nigeria. The study concludes that prostate cancer issues were not given adequate coverage and prominence during the period of study in Nigerian newspapers. Against this backdrop, the researchers recommended that Nigerian newspapers should report more news stories on prostate cancer in Nigeria using feature news format and in-depth interpretation. This will make the public to be informed and educated, thereby taking precautionary measures to curtail or prevent prostate cancer.